Review of the Role of Forensic Medicine in Sexual Violence Crime Cases - Ditya Nisa Rohmah (Proceedings Series on Social Sciences & Humanities, 2023)
The crime of embezzlement of rental cars that has recently occurred is very troubling to car rental owners. This is a problem where the meaning of a rule of law if crimes committed by the community cannot be followed by the rule of law, such as crimes by embezzlement is one of the types of crimes against human property regulated in Article 372 of the Criminal Code. Therefore, law enforcement against the crime of embezzlement of rental cars must be resolved thoroughly with justice, as well as for the creation of good and fair law enforcement before the law. The research objectives are as follows: 1) To find out how law enforcement related to the crime of embezzlement of rental cars. 2) To find out how the perpetrator's responsibility for the crime of embezzlement of rental cars. This research uses a normative juridical approach, which is used to make clear, systematic and precise descriptions of the facts / characteristics of certain regions and populations which are then analyzed to obtain the desired facts. The research method used: literature study by reading books, studying, quoting, analyzing what is obtained from book literature. The result of this research is the application of Article 372 of the Criminal Code in the criminal act of embezzlement of rental cars where the criminal act committed by the tenant against the rental goods belonging to the rental owner is due to an abuse of trust where the criminal act of embezzlement is regulated in the provisions of Article 372 of the Criminal Code.